18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Accuracy in the Staging of Non-Small Cell Lung Cancer: Review and Cost-Effectiveness. (5th November 2014) - Gómez León, Nieves; Escalona, Sofía; Bandrés, Beatriz; Belda, Cristobal; Callejo, Daniel; Blasco, Juan Antonio
Abstract : Aim of the performed clinical study was to compare the accuracy and cost-effectiveness of PET/CT in the staging of non-small cell lung cancer (NSCLC). Material and Methods . Cross-sectional and prospective study including 103 patients with histologically confirmed NSCLC. All patients were examined using PET/CT with intravenous contrast medium. Those with disease stage ≤IIB underwent surgery (n = 40 ). Disease stage was confirmed based on histology results, which were compared with those of PET/CT and positron emission tomography (PET) and computed tomography (CT) separately. 63 patients classified with ≥IIIA disease stage by PET/CT did not undergo surgery. The cost-effectiveness of PET/CT for disease classification was examined using a decision tree analysis. Results . Compared with histology, the accuracy of PET/CT for disease staging has a positive predictive value of 80%, a negative predictive value of 95%, a sensitivity of 94%, and a specificity of 82%. For PET alone, these values are 53%, 66%, 60%, and 50%, whereas for CT alone they are 68%, 86%, 76%, and 72%, respectively. Incremental cost-effectiveness of PET/CT over CT alone was €17, 412 quality-adjusted life-year (QALY). Conclusion . In our clinical study, PET/CT using intravenous contrast medium was an accurate and cost-effective method for staging of patients with NSCLC.